Endarterectomy for Iliac Occlusive Disease during Kidney Transplantation: A Multicenter Experience - Sorrells, William S.; Mao, Shennen A.; Taner, Timucin; Jadlowiec, Caroline C.; Farres, Houssam; Davila, Victor; Money, Samuel R.; Stone, William M.; Al-Khasawneh, Mohammad; Da Rocha-Franco, Joao A. Da Rocha; Oldenburg, Warner A.; Oderich, Gustavo S.; Taner, C. Burcin; Hakaim, Albert G.; Erben, Young (International Journal of Angiology, 2020)
Little is known about the surgical challenges and outcomes of kidney transplantation (KT) in the face of severe iliac occlusive disease (IOD). We aim to examine our institution's experience and outcomes compared with all KT patients. Retrospective review of our multi-institutional transplant database identified patients with IOD requiring vascular surgery involvement for iliac artery endarterectomy at time of KT from 2000 to 2018. Clinical data, imaging studies, and surgical outcomes of 22 consecutive patients were reviewed. Our primary end-point was allograft survival. Secondary end-points included mortality and perioperative complications. A total of 6,757 KT were performed at our three sites (Florida, Arizona, and Minnesota); there were 22 (0.32%) patients receiving a KT with concomitant IOD requiring iliac artery endarterectomy. Mean patient age was 61.45 ± 7 years. There were 13 (59.1%) male patients. The most common etiology of renal failure was diabetic nephropathy in 10 patients (45.5%) followed by a combination of hypertensive/diabetic nephropathy in five patients (22.7%), and hypertensive nephrosclerosis in three patients (13.6%). The majority (n = 16, 72.7%) of patients received renal allografts from deceased donors and six (27.3%) were recipients from living donors. Mean time from dialysis to transplantation was 2.9 ± 2.9 years. Mean follow-up was 3.5 ± 2.5 years. Mean length of hospital stay was 6.3 ± 4.3 days (range: 3–18 days). Graft loss within 90 days occurred in two (9.1%) patients, one due to renal vein thrombosis and another due to acute tubular necrosis. Overall allograft survival was 90.1% at 1-year and 86.4% at 3-year follow-up. Overall mortality occurred in 6 (27.3%) patients. Perioperative complications (Clavien-Dindo Grade 2–4) occurred in 13 (59.1%) patients, including 10 (45.5%) with acute blood loss anemia requiring transfusion, 2 (9.1%) reoperations for hematoma evacuation, 1 (4.5%) ischemic colitis requiring total abdominal colectomy, and 1 (4.5%) renal vein thrombosis requiring nephrectomy. IOD patients selected for KT are not common and although challenging, they have similar outcomes to our standard KT patients. The 1- and 3-year allograft survivals were 90.1 and 86.4% versus 96.0 and 90.3% in the general KT patient population. With these excellent outcomes, we recommend expanding the criteria for KT to include patients with IOD with prior vascular surgery consultation to prevent progression of IOD or prevention of wait list removal in select patients who are otherwise good candidates for KT.
Keywords: peripheral arterial disease; renal failure; transplant